Hotspot spectral indices - Sandell, M; Leahy, J (2002)
In this contribution we present some interim results concerning the spectral indices of the hot-spots of high redshift radio galaxies and quasars. This work forms a part of the Distant DRAGNs Survey, a project to map at sub-kpc resolution a sample of z > 1.5 radio galaxies and quasars drawn from multiple flux-density-limited samples.